Development of a culture techniques for Tubificid worm, under laboratory conditions (Bangladesh Journal of Zoology, 2015)
Study has been conducted to establish a suitable culture technique for Tubificid worm, Tubifex tubifex using different culture media. Cowdung, Rawfish and vegetables were evaluated as culture medium. Each medium was supplied as supplementary food at the rate of 250 mg/cm2 per week for 145 days. Water temperature, pH and ammonia of the rearing media ranged from 27.1-31.670C, 5.76-7.35 and 0.5 -